The Going Enterprise Paradox: Stability and Instability Under Money Manager Capitalism. Issue 4 (2nd October 2018) - Dean, Erik
Abstract: This article argues that the business enterprise has evolved through successive stable organizational structures which correspond with instability for those falling outside its aegis. This is shown in the institutional and historical context of both managerial capitalism in the mid-twentieth century as well as the era of financialization that followed. Hence, the framework developed herein elaborates on the ceremonial characteristics of the business enterprise under money manager capitalism, and constitutes a contribution toward an updated going concern theory of the business enterprise.